Effects of levels of graduate education on performance of faculty in instruction, research and extension services - Bautista, Nicolas Rapanot 1939-
The subjects are all the teachers in all public and private tertiary institutions in Central Mindanao. Graduate education was measured in terms of the level of education attained by the faculty: Level A constituted those with advanced degrees (i.e., master's and doctorate), Level B those with non-completed graduate studies; and the control group, Level C included those with no advanced educational training except basic degrees. Faculty members with graduate degrees (Level A) consistently and significantly outperformed those with limited (Level B) or those without (Level C) graduate studies in all the three basic school functions of instruction, research and extension.